The experiences in the family of origin and the early maladaptive schemas as predictors of marital violence in men and women - Paim, Kelly Cardoso (2018)
Marital violence is a worldwide issue that affects several economic, racial and ethnic groups. Assuming that the marital violence dynamics is interactive, this study aims to identify the predicting variables of the phenomenon, through the perspective of the Theory of Schemas by Jeffrey Young. This way, the importance of experiences within the family of origin as well as the Early Maladaptive Schemas predicting marital physical violence between men and women were investigated. There was a sample made up of 181 men and 181 women and the instruments applied for data collection were: Young Schema Questionnaire (YSQ-S3) and Revised Conflict Tactics Scale (CTS2). The analysis of the results was carried out through multiple regression analysis with the stepwise methodology. The results show that the defectiveness/shame schema in both men and women and the mistrust/abuse schema in men are predicting variables of the violence committed against the spouse. A longer adjustment in mothers was considered the protective variable of violent behaviors among women. Regarding the victimization of the violence, the defectiveness/shame schema in both men and women and the Mistrust/Abuse schema in men are predicting variables of the violence suffered in the intimate relationships. More functionality in the decision-making styles of mothers was identified as a violencevictimization protector among women. The outcome of this study amplifies the discussion on the variables which can identify the marital violence phenomenon, consolidating the importance of the Early Maladaptive Schemas in the marital violence.